Social Consequence of Inter-caste Marriage: A Case Study of Itahari, Sunsari - Poudel, Tanka Mani (Dristikon: A Multidisciplinary Journal, 2023)
Marriage is typically understood to be a sexual and financial relationship that is socially accepted, considered to be more or less permanent, and that implies rights and obligations for the married couple and any children they may have. The Eastern Development Region's urban area serves as the basis for this study. For this study, a total of 30 couples were purposefully chosen as respondents. Eight couples were asked to participate in a thorough study using the case study technique in order to obtain qualitative information about inter-caste marriage and its effects on the personal, professional, and social lives of couples. My research has demonstrated that non-Dalit families are more likely to accept a son-in-law than a daughter-in-law. Because of the family's weak familial network, exposure to the outside world, and the presence of power and status in a very important family, which could overshadow the violation of societal standards? Non-Dalit women who were not able to visit their birth homes on special events like Teej, Bhaitika, and Dasahin felt a loss of kinship relationship because hypogamous marriages are not approved by the natal family.